2018
DOI: 10.1177/2050157918804844
|View full text |Cite
|
Sign up to set email alerts
|

Remembering the voice: Exploring information and sentiment in voicemail archival practices

Abstract: This study examines preservation of voicemail artifacts. Applying an exploratory approach through grounded theory, participants ( N = 52) from Amazon’s Mechanical Turk provided common reasons for retaining voicemail artifacts. Results highlighted why participants retained or deleted general and specific voicemails. Five categories,  past-focused, important, future-focused, sentimental, and neglectful, represented retaining reasons. The oldest and most important artifacts represented sentimental messages. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Researchers have argued that online intimacy transcends proximal and temporal limitations creating the ability to continue closeness and connectivity. LeFebvre and Haggadone (2018) explored the reasons why people kept or deleted specific voicemails and found that some of the most beloved retained messages were the oldest ones. They also found that many unwanted voicemails were soon deleted after their creation, thereby suggesting that people, at least in part, actively choose to distance themselves from reminders of negative events, experiences, or relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have argued that online intimacy transcends proximal and temporal limitations creating the ability to continue closeness and connectivity. LeFebvre and Haggadone (2018) explored the reasons why people kept or deleted specific voicemails and found that some of the most beloved retained messages were the oldest ones. They also found that many unwanted voicemails were soon deleted after their creation, thereby suggesting that people, at least in part, actively choose to distance themselves from reminders of negative events, experiences, or relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, questions of how digital media transform human relationships to death have also generated important research into the accounting, experience and memorialization of human death (Arnold et al, 2018). Some research centers on processes of commemoration, such as saving voicemails of those who have died (LeFebvre and Haggadone, 2019). In other instances, the death itself is pathologized, such as when those who die while in the process of taking a ‘selfie’ (Maddox, 2017; Scott, 2018).…”
Section: A Matter Of Lifelogging and Deathloggingmentioning
confidence: 99%